Mobile Banking in Madagascar: Potential Benefits and Challenges - Rakotoarisoa, Maminiaina Heritiana Sedera; Hajaina, Ravoaja (The Indonesian Institute of Science and Technology Research, 2023)
The existence of mobile banking promotes financial inclusiveness and upgrades the financial literacy of individuals. Mobile banking has drastically grown in the decades both in developed and developing nations. This fast pace of growth is a result of raising various types of products and services related to mobile money for users. In this work, we present additional information that needs to be understood about mobile banking in the context of Madagascar, Africa. The aim of this paper is to provide an overview of the potential benefits and challenges faced in adopting mobile banking. Understanding the current issues of mobile banking contributes to the advancement of theory and scientific knowledge in banking and finance. In addition to the contribution of this work to the literature on mobile banking, this yields insightful and comprehensive knowledge for the government, central banks, commercial banks, and other financial institutions in forming new strategies to improve the financial system and cope with technological advancement.